Asset-based youth support—reclaiming the roots of youth work at the Foyer Federation - Stuart, Kaz (Cogent social sciences, 2017)
Evolutionary systems theory is widely accepted as the organising principle for life sciences. In more recent years it has also been applied to economics, culture, language, and leadership. In this paper we argue that services for young people need to evolve from deficit discourses to asset-based practices. The argument for asset-based work with young people will be presented through the lens of one organisation, the Foyer Federation who were developing asset-based service design. The findings of a systematic literature review are presented to demonstrate the scope and impact of current asset-based initiatives globally. The assumptions and activities of deficit and asset-based approaches are contrasted with use of cultural-historical activity theory. These findings are synthesised with the developmental work of the Foyer Federation to explicate the philosophy and practice of asset-based work with young people. The findings and implications are drawn out to inform others practice and research.